2021
DOI: 10.1007/s13365-021-00973-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of enteroviruses and predominance of echovirus 30 in an Iranian population with aseptic meningitis

Abstract: Human enteroviruses are the most prevalent causes of aseptic meningitis worldwide. However, despite such predominancy, defining the enteroviral etiology of aseptic meningitis remains a diagnostic dilemma for the clinician in Iran. Therefore, this study was conducted to characterize the prevalence and clinical significance of enteroviral aseptic meningitis as well as the predominant enterovirus serotypes among patients with aseptic meningitis in the South of Iran. Cerebrospinal fluid (CSF) specimens were obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
1
7
1
Order By: Relevance
“…Compared with the manual method, the nucleic acid extraction kit is able to remove PCR inhibitors effectively. 33 In this study, the prevalence of occult HBV infection among hemodialysis patients was not statistically associated with duration of hemodialysis, age, gender distribution, and level of education, although the prevalence of HBV infection was higher in patients with 1 to 2 years on regular hemodialysis, the hemodialysis patients aged 40 to 49 years, female hemodialysis patients, and upper diploma patients. Similarly, recent studies in Zanjan (West of Iran) and Qazvin (West-Center of Iran) demonstrated that the prevalence of occult HBV infection among hemodialysis patients is not associated with age, gender, or duration of hemodialysis.…”
Section: Discussioncontrasting
confidence: 51%
“…Compared with the manual method, the nucleic acid extraction kit is able to remove PCR inhibitors effectively. 33 In this study, the prevalence of occult HBV infection among hemodialysis patients was not statistically associated with duration of hemodialysis, age, gender distribution, and level of education, although the prevalence of HBV infection was higher in patients with 1 to 2 years on regular hemodialysis, the hemodialysis patients aged 40 to 49 years, female hemodialysis patients, and upper diploma patients. Similarly, recent studies in Zanjan (West of Iran) and Qazvin (West-Center of Iran) demonstrated that the prevalence of occult HBV infection among hemodialysis patients is not associated with age, gender, or duration of hemodialysis.…”
Section: Discussioncontrasting
confidence: 51%
“…Historically, EVs were firstly known as causative agents of PVM during the early sixties of the last Gregorian century (108). Later, they were confirmed in several epidemiological investigations to constitute the primary cause of VM in children (7,(32)(33)(34). In the Middle East region, most of the PVM cases were also attributed to the EVs group of viruses (10)(11)(12)(13)(14)(15)109).…”
Section: Definitionsmentioning
confidence: 80%
“…EV is the primary pathogen causing aseptic meningitis, 34 and the main EV serotypes of causative agents for HFMD often overlap with those of aseptic meningitis 35 . E30 is one of the most common pathogens causing aseptic meningitis outbreaks 36–38 . Since the 2008 HFMD outbreaks, E3 and E30 were often detected in HFMD cases 19,25,26,39,40 .…”
Section: Discussionmentioning
confidence: 99%